Differentiated trust in today's schools - Yavas, Tuba; Celik, Vehbi (Elsevier Science Bv, 2010)
Dynamic settlements in educational sciences indicate that along with the phenomenon of violence, today's schools pass through a process of mistrust. Trust is considered as one of the investment tools of today's schools. Five essential features of the concept of trust and 'trust adjustment' in secondary education institutions within the frame of differentiated trust are examined and analyzed in this study. This research investigated the degree of organizational trust and differentiated trust 56 principals, 463 teachers and 13.877 students in public secondary schools in Mus, Turkey in the 2008-2009 academic year. The results showed that while the administrators have high degree of trust, teachers and students have moderate degree of trust. This implies that administrators should be able to promote different dimensions of trust for different levels and so, they will be able to exhibit an effective leadership by adjusting school's 'trust tone'. (C) 2010 Elsevier Ltd. All rights reserved.
2nd World Conference on Educational Sciences (WCES-2010) -- FEB 04-08, 2010 -- Bahceschir Univ, Istanbul, TURKEY
Keywords: Secondary schools; organizational trust; differentiated trust